Implementasi Regulatory Impact Assessment (RIA) Sebagai Upaya Menjamin Partisipasi Masyarakat Dalam Penyusunan Peraturan Daerah - Nasokah Nasokah (Fakultas Hukum Universitas Islam Indonesia, 2008)
Regulatory Impact Assessment (RIA) is independently institutionalized as a quality control for local ordinances, be it for the draft of such ordinances or for those which are the established ordinances. RIA guides the logics and reasons in legislation process of a regulation without altering the existing mechanisms and institutions related to the issuance of a regulation